Employment effects of minimum wages - David Neumark (IZA World of Labor, 2018)
The potential benefits of higher minimum wages come from the higher wages for affected workers, some of whom are in poor or low-income families. The potential downside is that a higher minimum wage may discourage employers from using the low-wage, low-skill workers that minimum wages are intended to help. If minimum wages reduce employment of low-skill workers, then minimum wages are not a "free lunch" with which to help poor and low-income families, but instead pose a tradeoff of benefits for some versus costs for others. Research findings are not unanimous, but evidence from many countries suggests that minimum wages reduce the jobs available to low-skill workers.
Keywords: 330; minimum wage; employment effects